APLIKASI PUPUK BOKASHI DAN NPK ORGANIK PADA TANAH ULTISOL UNTUK TANAMAN PADI SAWAH DENGAN SISTEM SRI (System of Rice Intensification) - Siti Zahrah (Jurnal Ilmu Lingkungan, 2011)
This research was conducted in the Experimental Field, Faculty of Agriculture, Riau IslamicUniversity and Soil Laboratory, BPTP Riau Province from October 2008 to February 2009.The research aim to study the effect of bokashi and NPK organic fertilizer to N, P, K uptakeand rice yield in Ultisol with SRI (System of Rice Intensification). The experimental with Completely Randomized Design for Factorial 4 x 4 were used. The first factor was bokashifertilizer addition, consisting of four levels (0, 10, 20, 30 ton ha-1) and second factor wasorganic NPK fertilizer addition, consisting of four levels (0, 200, 400, 600 ha -1). The result ofresearch indicates that: (1) Interactian effect of treatment was significant to N, P, K uptake,productive stem, length of stalk, grain/stalk, weight of dried seed, and weight of 1000 seeds.(2) The best treatment was addition of bokashi (30 ton ha-1) and organic NPK fertilizer (600kg ha -1) with productive stem (19,0 stems/plant), grain/stalk (210,7 grain), filled out seed(97,63%), weight of dried seed (94,35 g/plant) and weight of 1000 seeds (29,6 g)